Incidence of Clavicle Fractures in Sports: Analysis of the NEISS Database - Van Tassel, D.; Owens, B. D.; Pointer, L.; Moriatis Wolf, J. (International Journal of Sports Medicine, 2014)
Our goal was to present current data on the incidence of clavicle injuries presenting for urgent evaluation and to report the sports activities associated with injury. Using the National Electronic Injury Surveillance System (NEISS) database, the number of clavicle fractures presenting to a representative sample of US hospitals was retrospectively calculated and weighted estimates used to extrapolate this data to the US population. Incidence estimates were obtained using validated analyses and US census data, with sports injuries being noted and fractures stratified by sport. A total of 9 428 fractures of the clavicle were reported, representing 357 155 injuries in the US population over 5 years. The estimated incidence of clavicle fractures in the US presenting for emergency care is 24.4 fractures per 100 000 person-years (95% confidence intervals (CI), 22.8–26.1). The peak incidence was highest between ages 10–19 years. Men were nearly 3 times as likely to sustain a clavicle fracture. Sports were a factor in 45% of all clavicle fractures. In sports-related injuries, 16% of fractures occurred from bicycling, followed by football (12%) and soccer (6%). In summary, injuries from bicycling were the most common cause of clavicle fracture, followed by contact sports. Male gender and younger age are risk factors for clavicle fractures.
Keywords: clavicle fracture; epidemiology; sports-related